Assessment of rock mass quality and its effects on charge ability using drill monitoring technique - Ghosh, Rajib (Luleå tekniska universitet, Geoteknologi, 2017)
For an efficient mining operation, it is essential to have as much information as possible aboutthe ore to be excavated and the rock masses surrounding the ore. Geological information andthe content and distribution of extractable minerals, are central concerns for long term mineplanning. However, for mine stability and production scheduling, the mechanical conditionsof ore and side rock are also very important. The underground mining process normallyconsists of a number of unit operations, such as drilling, charging, blasting, loading,transportation, hoisting etc., linked in a production chain. The quality of the initial operations(drilling, charging and blasting) normally defines the pre-conditions for the following loadingand transportation processes in the mine. The ability to fully charge holes as planned has beenidentified as one of the major obstacles for smooth fragmentation. Course or unevenfragmentation will, for example, significantly affect the loading and transportation efficiencyin the downstream production chain.Earlier studies in LKAB’s Malmberget mine have shown that the chargeability is on averagearound 90%. However, individual levels can have an average chargeability of only 70% andindividual rings, at those levels, can suffer from chargeability as low as 50%. A significantpart of these problems has its origin in geo-mechanical problems in the rock mass. Therefore,detailed knowledge of the rock mass condition surrounding the boreholes is essential toimprove the planning and execution of the charging works in a mine and to improve overallfragmentation and production efficiency.The focus of this thesis is therefore to define and evaluate geo-mechanical features in thedrilled rock mass effecting chargeability, and to evaluate drill monitoring technique for theassessment of rock mass quality and its effects on borehole’s chargeability using hydraulic In-The-Hole (ITH) percussive drilling.The research is based on literature review, drill-monitoring data, borehole filming, on-lineproduction database ...